Correlation Of Waist Hip Ratio and BMI With Hypertension and Diabetes Mellitus in An Urban Area of Bangalore City - Patil, Savita S; Rajaram, Dinesh R; Nandakumar BS; Seeri, Jayasree S (National Journal of Community Medicine, 2015)
Background and Objective: BMI and WHR are most widely used measures to define obesity and predict its complications, such as diabetes and hypertension. Hence study emphasized to know correlation among above parameters. Methods: A Cross sectional study conducted among 240 adults who screened for Hypertension, DM based on history and examination or both. Anthropometric measurements, Blood pressure, random blood glucose levels and ECG was recorded for individuals with suspected complications of cardiovascular diseases. Data was analyzed using SPSS 18 for descriptive, analytical statistics χ2 (P value) and Pearson’s correlation co-efficient. Results: 240 individuals attendant health checkup, 87 of them found to be hypertensives and/ or diabetic. Obesity was significantly high in females (65.2%, 95.6%) as compared to males (41.5%, 61%) with respect to both BMI and W/H ratio respectively. There was a statistical difference in obesity by BMI and WHR, where in 79% of the subjects showed high WHR as compared to only 54% by BMI. Similarly significant association was observed between Hypertension (X2= 4.09, P=0.04) and Waist Hip Ratio (X2=6.35,P=0.01). Complications were more common among obese patients as compared to non-obese patients. Conclusion: That there is correlation between WHR, BMI with hypertension and DM type 2 and also with cardiovascular complications. The significant association of WHR with HTN is an indication of importance of central adipose tissue in study population.